A novel free radical scavenger, NSP-116, ameliorated the brain injury in both ischemic and hemorrhagic stroke models - Takahiko Imai; Sena Iwata; Daisuke Miyo; Shinsuke Nakamura; Masamitsu Shimazawa; Hideaki Hara (Elsevier, 2019)
Reperfusion injury is a serious problem in ischemic stroke therapy, which leads to neuronal damage and intracranial hemorrhage (ICH). A novel free radical scavenger, NSP-116, has anti-oxidative effect and may ameliorate reperfusion injury. The purpose of this study was to investigate the effects of NSP-116 on both ischemic and hemorrhagic stroke models.First, we assessed whether NSP-116 has protective effects in vitro. Pre-treatment of NSP-116 decreased neuronal cell damage induced by H2O2 or LPS. Moreover, NSP-116 also suppressed mitochondria damage and apoptosis in H2O2-induced neuronal injury model. Based on these results, we used a middle cerebral artery occlusion (MCAO)-induced ischemic stroke model or a collagenase-induced ICH model. Using the MCAO model, we evaluated the cerebral blood flow (CBF), neurological deficit, and infarct volume. Hematoma volume was assessed at 3 days after ICH. In the MCAO model, oral administration of NSP-116 at 30 mg/kg attenuated the reduction of CBF, neurological deficits, and infarct formation. Interestingly, NSP-116 also ameliorated hematoma expansion and neurological deficits in the ICH model. Additionally, pre-treatment of NSP-116 suppressed the brain microvascular endothelial cell death induced by collagenase treatment.Collectively, our findings indicated that oral administration of NSP-116 attenuates both ischemic and hemorrhagic brain injuries after stroke. Keywords: Brain hemorrhage, Brain ischemia, Oxidative stress, A free radical scavenger, Stroke